The Importance of Ethical of Artifical Intelligence (AI) in Inslusive Education - Anita Intan Rohmatuszahroh; Kiki Ayu Hermawati; Hanny Rizqiyana Nur'aliya; Siti Khalimah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Artificial Intelligence (AI) has given new hopes and changed the elements of education for the better, especially in inclusive education. AI is very concerned with equality, which is expected to help children with special needs get their rights and a more appropriate education. However, the presence of AI has also brought many negative impacts due to the lack of understanding of the ethical principles that must be implemented. This paper was compiled to explore The Importance of Ethical of Artificial Intelligence (AI) in Inclusive Education. The results of this study show that until now there have been many public, private, and government organizations in various countries around the world that have created multiple guidelines to regulate, guide, and protect all elements involved and affected by the progress of AI. Among them are charter agreements and various guidelines related to ethical principles, basic rights, fundamental values, and other instruments that have been studied and compiled in detail and very systematically. But the conditions that have occurred until now are far from perfect. AI still presents many problems, concerns, and forms of unavoidable abuses, especially in inclusive education.